Increased Risk of Influenza Infection During Cold Spells in China: National Time Series Study - Haitao Wang; Mengjie Geng; Tamara Schikowski; Ashtyn Tracey Areal; Kejia Hu; Wen Li; Micheline de Sousa Zanotti Stagliorio Coelho; Paulo Hilário Nascimento Saldiva; Wei Sun; Chengchao Zhou; Liang Lu; Qi Zhao; et al. (JMIR Publications, 2024)
Abstract BackgroundStudies have reported the adverse effects of cold events on influenza. However, the role of critical factors, such as characteristics of cold spells, and regional variations remain unresolved. ObjectiveWe aimed to systematically evaluate the association between cold spells and influenza incidence in mainland China. MethodsThis time series analysis used surveillance data of daily influenza from 325 sites in China in the 2014‐2019 period. A total of 15 definitions of cold spells were adopted based on combinations of temperature thresholds and days of duration. A distributed lag linear model was used to estimate the short-term effects of cold spells on influenza incidence during the cool seasons (November to March), and we further explored the potential impact of cold spell characteristics (ie, intensity, duration, and timing during the season) on the estimated associations. Meta-regressions were used to evaluate the modification effect of city-level socioeconomic indicators. ResultsThe overall effect of cold spells on influenza incidence increased with the temperature threshold used to define cold spells, whereas the added effects were generally small and not statistically significant. The relative risk of influenza-associated with cold spells was 3.35 (95% CI 2.89‐3.88), and the estimated effects were stronger during the middle period of cool seasons. The health effects of cold spells varied geographically and residents in Jiangnan region were vulnerable groups (relative risk 7.36, 95% CI 5.44‐9.95). The overall effects of cold spells were positively correlated with the urban population density, population size, gross domestic product per capita, and urbanization rate, indicating a sterner response to cold spells in metropolises. ConclusionsCold spells create a substantial health burden on seasonal influenza in China. Findings on regional and socioeconomic differences in the health effects of cold spells on seasonal influenza may be useful in formulating region-specific public health policies to address the hazardous effects of cold spells.